Togo : Third Review under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2018)
Economic activity shows incipient signs of stabilization in some sectors while it remains weak in others. The fiscal consolidation efforts continued and the domestic primary balance at end-June 2018 improved by 0.3 percent of GDP relative to the same period in 2017. Inflation has turned positive at 0.9 percent in September 2018 and is expected to remain below the WAEMU convergence criterion of up to 3 percent during the program period. The government is revisiting its strategy on the two public banks and is relaunching their privatization. The socio-political tensions have abated but the situation remains uncertain, particularly in light of the upcoming elections at end-2018.